COMPARATIVE ANALYSIS OF INTERNATIONAL PRACTICES FOR IMPROVING RESOURCE EFFICIENCY IN INDUSTRIAL ENTERPRISES (Global Conference on Multidisciplinary Research and Innovation, 2026)
This study presents a comparative analysis of international experience in improving the economic efficiency of resource utilization in industry using the examples of Sweden, Singapore, and South Korea. The study examines modern approaches to industrial resource management, including green industrial transformation, energy efficiency systems, and smart manufacturing technologies. Particular attention is paid to the possibility of adapting international practices to developing economies. analyzes the impact of digital transformation on productivity growth in global apparel value chains. The study focuses on the application of advanced technologies such as artificial intelligence, automation systems, and digital supply chain platforms in the textile and garment industry. In the context of globalization, apparel production is organized through complex international networks, where efficiency depends on coordination, information flow, and technological integration. The research is based on the analysis of international reports and academic literature from international organizations.
Keywords: resource efficiency, industrial development, smart manufacturing, energy efficiency, green industry, Sweden, Singapore, South Korea